A study of indigenous sorghum agriculture in Southern Africa: combining isotope and indigenous knowledge systems approaches - Masemula, Nandi (Department of Archaeology, 2024)
Sorghum and millets were the principal grain crops of sub-Saharan African farming societies. Enquiry into their isotopic variability is scant and some of the work that has been done is based on studies in highly controlled, artificial environments. To help fill this gap, the present study investigates the variation in δ13C and δ15N in three varieties of sorghum, mshalane, 236 and 308. These were cultivated at four localities in different regions of Eswatini and South Africa, either by small-scale traditional farmers or in accordance with their methods. In addition, this study includes carbon and nitrogen isotopic analysis of archaeological sorghum grains from the mid-19th century Historic Cave siege site. The study also explores the impact that choice of agricultural practices and methods of grain storage and food preparation may have on the δ13C and δ15N values of sorghum. To this end, semi-structured interviews were conducted with 18 contemporary small-scale agriculturalists from eastern Eswatini. The range of δ13C values in the contemporary-grown sorghum from summerrainfall regions of South Africa is 1.7‰ (n=90), and the mshalane variety shows the greatest sensitivity to environmental variation. Archaeological sorghum grains from Historic Cave yield δ13C values approximately 1.1‰ less negative than contemporary-grown sorghum (after correction for variation in atmospheric δ13C), which likely reflects particular agricultural practices and/or the cultivation of sorghum varieties with characteristically higher δ13C values by the Kekana Ndebele. The range of δ15N values in both contemporary (5.4‰, n=90) and archaeological (8.7‰, n=11) sorghum is larger than that usually attributed to a single trophic level, with significant implications for the interpretation of δ15N in consumers. Some methods of sorghum storage and preparation involve fermentation, which may increase isotopic variation further. These results will contribute towards achieving improved isotope-based dietary reconstructions in African Iron Age farming communities.